The Effect of Smoking and Opioid Consumption on the Severity of the Disease and Duration of Hospitalization in COVID-19 Patients - Fayazi H. S.; Naeimi A.; Yaseri M.; Khatibani S. S. M. (Acta Medica Bulgarica, 2023)
In the Coronavirus 2019 (COVID-19) global pandemic, various studies on the target communities of this virus were widely started and rapidly progressed. Smokers and opioid consumers are one of the virus targets since they have a vulnerable respiratory system. Due to the contradictory results in previous studies and the lack of similar investigations in this area, we aimed to perform this study to investigate the effect of smoking and opioid consumption on the consequences of the COVID-19 disease.